2015
DOI: 10.1152/ajpheart.00023.2015
|View full text |Cite
|
Sign up to set email alerts
|

Coronary vasomotor responses to isometric handgrip exercise are primarily mediated by nitric oxide: a noninvasive MRI test of coronary endothelial function

Abstract: Hays AG, Iantorno M, Soleimanifard S, Steinberg A, Schär M, Gerstenblith G, Stuber M, Weiss RG. Coronary vasomotor responses to isometric handgrip exercise are primarily mediated by nitric oxide: a noninvasive MRI test of coronary endothelial function. Am J Physiol Heart Circ Physiol 308: H1343-H1350, 2015. First published March 27, 2015 doi:10.1152/ajpheart.00023.2015.-Endothelial cell release of nitric oxide (NO) is a defining characteristic of nondiseased arteries, and abnormal endothelial NO release is bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
81
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 38 publications
(85 citation statements)
references
References 35 publications
4
81
0
Order By: Relevance
“…The values for CEF are similar to those obtained in our prior CMR studies, demonstrating a coronary vasodilatory response to IHE in the healthy subjects, and no vasodilatory response or a vasoconstrictor response in many CAD patients [16, 17, 22]. We previously showed that the administration of nitroglycerin, an endothelial independent stressor, caused normal vasodilatation in coronary segments with mild to severe CAD that exhibited abnormal responses to IHE.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The values for CEF are similar to those obtained in our prior CMR studies, demonstrating a coronary vasodilatory response to IHE in the healthy subjects, and no vasodilatory response or a vasoconstrictor response in many CAD patients [16, 17, 22]. We previously showed that the administration of nitroglycerin, an endothelial independent stressor, caused normal vasodilatation in coronary segments with mild to severe CAD that exhibited abnormal responses to IHE.…”
Section: Discussionsupporting
confidence: 84%
“…Recent studies demonstrate that CMR measures of CEF performed during isometric handgrip exercise (IHE) quantify nitric-oxide mediated coronary endothelial vasoreactivity [16] with excellent short- and longer-term reproducibility [17, 18]. …”
Section: Introductionmentioning
confidence: 99%
“…We recently reported that the coronary response to IHE is measurable with MRI 11,15,16 and mediated by NO in healthy individuals 17 . Because it was not previously known whether the IMA response to IHE is NO-mediated 27 , we report here that the NOS inhibitor L-NMMA abolishes the normal IMA vasodilatory and blood flow IHE responses in healthy subjects (Fig 2).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we recently demonstrated in vivo that the coronary artery response to IHE is reproducible and primarily NO-mediated because it is blocked by the nitric oxide synthase (NOS) inhibitor monomethyl-L-arginine (L-NMMA) in healthy subjects 17 .…”
mentioning
confidence: 99%
“…The lack of information on this topic stems from the difficulty in attaining such measures during exercise, especially in healthy humans. However, a recent investigation by Hays et al [112] reported that coronary vasodilation during ischemic handgrip exercise in healthy humans is primarily NO-mediated (Figure 6). Although not directly examined in this study, factors that attenuate NO-bioavailability and alter redox balance, including free radicals, would be expected to impair coronary vasodilation, mimicking the attenuated vasodilation exhibited by patients with coronary artery disease during ischemic handgrip exercise.…”
Section: Free Radical Regulation Of Coronary Blood Flowmentioning
confidence: 99%